Research Civil Aircraft Model (RCAM) Dengan Metode Dinamis 6 Derajat Kebebasan Menggunakan MATLAB - Aulia Widya Prameswari; Arief Suryadi Satyawan; Denden Mohamad Ariffin (Akademi Angkatan Udara, 2021)
The Aircraft Model is an attempt to create or simulate an actual aircraft and this model can be called the Research Civil Aircraft Model (RCAM), which is a twin-engine civil aircraft model developed by the Group for Aeronautical Research and Technology in Europe (GARTEUR). This aircraft model is similar to the Boeing 757-200. Research Civil Aircraft Model created using 6 degrees of freedom. 6 degrees of freedom consist of 3 translations, namely 3 degrees for Cartesian coordinates on the axis (x,y,z) and 3 rotations, namely 3 degrees (pitch, roll, and yaw) which are used to control surface deflection and throttle position. To create a model, parameters are needed, namely the parameters of the mass of the aircraft and the parameters of the aero chord and also the CoG (Center of Gravity) of an aircraft. The algorithm entered comes from control limits/Saturation, Intermediate Variables, Force Coefficients, Moment Coefficients, Propulsion Effects, Gravity Effects until finally simulated using